Reproductive Biology Aspect of Freshwater Shrimp (Macrobrachium mammilodactylus) from the Terminal AKAP Lake, Payung Sekaki District, Pekanbaru City - J. Wiratama, Prano; Windarti, Windarti; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractMacrobrachium mammilodactylus is a type of freshwater shrimp that inhabits the Terminal AKAP Lake. The population of freshwater shrimp in this lake is relatively high and its indicate that reproduction of the shrimp was succeed. To understand the reproduction biology of the shrimp, a study has been carried out from February to March 2018. Sampling were conducted 4 times, once/week. Totally 107 shrimps (26 male and 81 female) were captured, they were 23.31-47.50 mm TL. and 0.1932-1.2132 gr BW. Sex ratio of males and females was 1:3.1. In each sampling time there were shrimps with 2nd, 3rd and 4th maturity level. Gonad Somatic Index (GSI) of the male was ranged from        0.80-3.19% and that the female was ranged from 0.98-4.88%. Fecundity is around 128-273 eggs/shrimp and the egg diameter was 0.43-0.73 mm. There were 27 ovigerous females that carried 13-289 eggs/female. The diameter of carried egg was 0.50-1.25 mm with embryo development in stage I (the embryo with no eye) and II (the embryo with developed eyes). The relationship of fecundity and TL toward BW are weak, r=0.39and r = 0.37respectively, while the relationship between fecundity and Gonad Weight was strong (r = 0.84). There were ovigerous females that had eggs in several developing stages inside their ovary, and it indicates that M. mammilodactylus  is a partial spawner. Keyword: Freshwater shrimp, sex ratio, maturity level,GSI, fecundity